1999
DOI: 10.1006/jmbi.1998.2601
|View full text |Cite
|
Sign up to set email alerts
|

Coevolving protein residues: maximum likelihood identification and relationship to structure 1 1Edited by G. Von Heijne

Abstract: The identi®cation of protein sites undergoing correlated evolution (coevolution) is of great interest due to the possibility that these pairs will tend to be adjacent in the three-dimensional structure. Identi®cation of such pairs should provide useful information for understanding the evolutionary process, predicting the effects of site-directed substitution, and potentially for predicting protein structure. Here, we develop and apply a maximum likelihood method with the aim of improving detection of coevolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
198
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(206 citation statements)
references
References 25 publications
5
198
1
Order By: Relevance
“…Several early studies identified within-protein correlations among amino acid positions but did not account for phylogenetic relationships (Korber et al 1993;Neher 1994). More recent studies have identified co-occurring substitutions within a phylogeny (Pollock 1999;Fukami-Kobayashi et al 2002;Dimmic et al 2005;Dutheil et al 2005;Yeang and Haussler 2007). Such patterns support within-protein epistatic interactions but do not distinguish among CN, CM, and CWS scenarios.…”
Section: Compensatory Protein Evolutionmentioning
confidence: 99%
“…Several early studies identified within-protein correlations among amino acid positions but did not account for phylogenetic relationships (Korber et al 1993;Neher 1994). More recent studies have identified co-occurring substitutions within a phylogeny (Pollock 1999;Fukami-Kobayashi et al 2002;Dimmic et al 2005;Dutheil et al 2005;Yeang and Haussler 2007). Such patterns support within-protein epistatic interactions but do not distinguish among CN, CM, and CWS scenarios.…”
Section: Compensatory Protein Evolutionmentioning
confidence: 99%
“…Indeed, although some more sophisticated models have been proposed (e.g., refs. [45][46][47][48][49][50], all commonly used phylogenetic models of long-term protein evolution assume that epistasis is absent so that sites evolve independently (51)(52)(53)(54)(55)(56).…”
mentioning
confidence: 99%
“…The variation along this column is then quantified by calculating the mutual information content (27,28,31). The variation can also be quantified by estimating the pairwise amino acid distance using probabilistic approaches and then, the correlation between the distance patterns between amino acid columns from the same or different proteins (29,32,33).…”
Section: Molecular Coadaptation: Millions Of Years Of Trial-error Evomentioning
confidence: 99%